2017
DOI: 10.1002/brb3.790
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin mitigates cerebral vasospasm and early brain injury following subarachnoid hemorrhage via inhibiting cerebral inflammation

Abstract: Background and PurposeSubarachnoid hemorrhage (SAH)‐induced cerebral vasospasm and early brain injury is a fatal clinical syndrome. Cerebral vasospasm and early brain injury are associated with inflammatory response and oxidative stress. Whether curcumin, which plays important roles to regulate inflammatory cytokines and inhibit oxidative stress, inhibits SAH‐induced inflammation and oxidative stress are largely unknown.MethodsAdult male rats underwent autologous blood injection into prechiasmatic cistern to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…In various states, such as aging [6], brain contusion [7], and AD [1516], astrocytes are activated, resulting in abnormal expression of AQP4 on astrocyte soma and processes around neuronal elements. Almost all SAH complications, including cerebral vasospasm, microcirculatory disturbance, microthrombosis, cerebral ischemia, hypoxia, and oxidative stress, can lead to astrocyte activation [121920293031]. Impairing vascular polarization of AQP4 has been shown to hamper glymphatic clearance of metabolic macromolecules, including Aβ and Tau, from the brain [67].…”
Section: Discussionmentioning
confidence: 99%
“…In various states, such as aging [6], brain contusion [7], and AD [1516], astrocytes are activated, resulting in abnormal expression of AQP4 on astrocyte soma and processes around neuronal elements. Almost all SAH complications, including cerebral vasospasm, microcirculatory disturbance, microthrombosis, cerebral ischemia, hypoxia, and oxidative stress, can lead to astrocyte activation [121920293031]. Impairing vascular polarization of AQP4 has been shown to hamper glymphatic clearance of metabolic macromolecules, including Aβ and Tau, from the brain [67].…”
Section: Discussionmentioning
confidence: 99%
“…What's more, more than 1/3 of aSAH patients suffered cognitive impairment and experienced a decline of quality of life . Cerebral vasospasm (CVS) and early brain injury (EBI) are regarded as the main causes of poor outcome of patients with aSAH . Accumulated evidences have showed that inflammatory response, oxidative stress and peripheral immune response are significantly associated with CVS and EBI .…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin longa, commonly referred as turmeric, is used widespread as an essential spice in food preparations mainly due to its medicinal properties. Curcumin exhibits a number of medicinal properties including anti-diabetic [1], anti-arthritic [2], anti-oxidant [3], anti-inflammatory [4], antimicrobial [5], anti-neurodegenerative [6]and anticancer [7]. Despite the widespread applications, the beneficial effects of curcumin are hampered by its poor bioavailability which results from its high metabolic and excretion rates, poor absorption and minimal water insolubility [8].…”
Section: Introductionmentioning
confidence: 99%